Assessing Regional Asset Management Practices in The Provincial Government of West Sulawesi: Insights from APIP Supervision Based on Permendagri No.19/2016 - Mediaty Mediaty; Ruslan Ruslan; Akbar Ulman; Mahfud Mahfud; ST. Faizah Ridwan (Program Pascasarjana Universitas Negeri Makassar, 2024)
Clear Description about regional wealth and basis for preparing financial report can be accomplished by good implementation of Regional Asset Management Practices. This research aim to assessing problem on regional asset management in the Provincial Government of West Sulawesi. The Research Method using quantitative analysis from data representation dan qualitative analysis from Permendagri No.19/2016. Conceptual analysis is carried out to data that show the weakness of asset management practices in The Provincial Government of West Sulawesi. These weaknesses include unoptimal of administration implementation by asset users and administrators, the potential loss of official vehicles that are still controlled by moved officials, not documented asset need in the RKBMD, unpaid vehicle taxes, the absence of decree for asset usage, and undocumented asset maintenance by regional asset maintenance cards.